2020
DOI: 10.1155/2020/5786053
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Network Pharmacology with Molecular Docking to Unravel the Active Compounds and Potential Mechanism of Simiao Pill Treating Rheumatoid Arthritis

Abstract: Objective. To explore the main components and unravel the potential mechanism of simiao pill (SM) on rheumatoid arthritis (RA) based on network pharmacological analysis and molecular docking. Methods. Related compounds were obtained from TCMSP and BATMAN-TCM database. Oral bioavailability and drug-likeness were then screened by using absorption, distribution, metabolism, and excretion (ADME) criteria. Additionally, target genes related to RA were acquired from GeneCards and OMIM database. Correlations about SM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 74 publications
(28 reference statements)
0
16
0
Order By: Relevance
“…Thus, the use of quercetin can correct the immune imbalance by regulating the secretion of Th1 and Th2 cytokines, which is expected to be a new treatment method for OLP. Many reports have demonstrated that decrease in the viability and migration of T lymphocytes, and increase in apoptosis after quercetin treatment is beneficial in the management of inflammatory diseases and cancer 31 , 46 , 47 . Based on our findings, we propose that high concentrations of quercetin inhibit cell proliferation and migration, and induce T lymphocyte apoptosis in OLP patients, which may explain the immunomodulatory effect of quercetin against OLP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the use of quercetin can correct the immune imbalance by regulating the secretion of Th1 and Th2 cytokines, which is expected to be a new treatment method for OLP. Many reports have demonstrated that decrease in the viability and migration of T lymphocytes, and increase in apoptosis after quercetin treatment is beneficial in the management of inflammatory diseases and cancer 31 , 46 , 47 . Based on our findings, we propose that high concentrations of quercetin inhibit cell proliferation and migration, and induce T lymphocyte apoptosis in OLP patients, which may explain the immunomodulatory effect of quercetin against OLP.…”
Section: Discussionmentioning
confidence: 99%
“…Network pharmacology is a new method of using bioinformatics to observe the interactions between drugs and diseases, providing a new logical guide and technical routes for the development of drugs 30 . Serval studies have used the network pharmacology to identify the mechanism of action of quercetin and systematically elucidate its role in the treatment of diseases, such as rheumatoid arthritis and Alzheimer's disease 31 , 32 . Unfortunately, there are a few reports on the relationship between quercetin and OLP.…”
Section: Introductionmentioning
confidence: 99%
“…It interferes with the transport of eosinophils and is usually produced by a variety of airway cells, especially airway epithelial cells (Kong et al, 2014). MMP9 can be released from activated white blood cells, reduce the level of E-cadherin in lung tissue (Xie X. et al, 2020) and by intervening in the accumulation of neutrophils and eosinophils. It can promote the killing of pathogens and inhibit excessive inflammation (Lu et al, 2008;Kong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Network pharmacology can be used to predict the correlation between targets and indications. The molecular docking technology that simulates the molecular structure at the molecular level and the dynamic level verifies the binding status between the targets ( Tang et al, 2020 ). Through the integrated analysis of them, we explore its mechanism of action in the treatment of mycoplasma pneumonia.…”
Section: Introductionmentioning
confidence: 99%
“…Simiao Powder (SMP) is a well-known prescription used in ancient China for the treatment of joint pain [ 9 ]. This prescription originated from Chengfang Biandu in the Qing Dynasty (1904 A.D.).…”
Section: Introductionmentioning
confidence: 99%